Risk Management Information System in Educational Institution: Agile Scrum Approach - Intan Dzikria; Luvia Friska Narulita; Achmad Rizal; Nabila Amanda Maharani; Yusrida Muflihah; Siti Mutrofin; Dian Anita Nuswantara; Meylia Elizabeth Ranu; Sri Setyo Iriani; Luqman Hakim (International Conference of Innovation and Community Engagement, 2024)
This study investigates the development of a Risk Management Information System (RMIS) for educational institutions using the Agile Scrum Methodology. The frequent regulatory changes and evolving risk management needs in educational environments require a flexible approach to system development. Agile Scrum, with its iterative and incremental process, was examined for its effectiveness in managing these changes. Data were collected through interviews and observations of Scrum sprints. The results of this study show that Agile Scrum can be used as a method for faster and rapidly changing requirements in the risk management process at educational institutions. This research contributes to both academic knowledge on Agile practices and provides practical insights for educational institutions seeking to improve their risk management systems.